Penerapan Akad Murabahah Bil Wakalah dalam Sistem Pembiayaan Modal Usaha Bank Syariah PT. BPRS Puduarta Insani Deli Serdang - Dara Puspita; Nursantri Yanti (Fakultas Ekonomi dan Bisnis Islam, 2023)
ABSTRACT The Islamic finance industry continues to grow in Indonesia and venture capital financing is the main focus in the development of the Islamic finance industry. Business capital financing is a form of financing that can assist entrepreneurs in obtaining capital to develop their business. In this contract, the Islamic bank acts as a representative to buy goods from third parties and sell them to customers with previously promised profits. The customer will pay the price of the goods plus profit within a certain mutually agreed period of time, and the customer pays in installments. This study uses qualitative methods and collects primary data with open and closed data collection techniques. The aim is to analyze the mechanism of implementing murabahah contract financing. The data used in this study came from direct interviews with employees and employees from the Marketing Department in the field of Account Officer PT. Puduarta Insani. In this case the research that has been produced and has obtained a lot of information from Islamic banks, it is said that PT. BPRS Puduarta Insani in theory has been fully implemented in accordance with DSN - MUI No. 4 of 2000, but seen from practice it is not fully appropriate. PT. BPRS Puduarta Insani implements murabahah contracts carefully and prudently in providing business capital financing to its customers, by upholding sharia principles. The process starts from the customer submitting a financing application to an assessment, survey, and financing committee stage to determine whether the application is approved or not. If approved, it is followed by making a contract/agreement between the customer and the bank. In conclusion, PT. BPRS Puduarta Insani applies murabahah contracts carefully and objectively in providing business capital financing in accordance with sharia principles.